How Education Works - Dron, John (Athabasca University Press, 2023)
In this engaging volume, Jon Dron views education, learning, and teaching through a technological lens that focuses on the parts we play in technologies, from language and pedagogies to computers and regulations. He proposes a new theory of education whereby individuals are not just users but co-participants in technologies—technologies that are intrinsic parts of our cognition, of which we form intrinsic parts, through which we are entangled with one another and the world around us. Dron reframes popular families of educational theory (objectivist, subjectivist, and complexivist) and explains a variety of educational phenomena, including the failure of learning style theories, the nature of literacies, systemic weaknesses in learning management systems, the prevalence of cheating in educational institutions, and the fundamental differences between online and in-person learning. Ultimately, How Education Works articulates how practitioners in education can usefully understand technology, education, and their relationship to improve teaching practice.